Trisodium phosphate dip, hot water dip, and combination dip with/without brushing on broiler carcass decontamination. (July 2017) - Singh, P.; Lee, H.C.; Silva, M.F.; Chin, K.B.; Kang, I.
Abstract: The purpose of this research was to evaluate the effects of trisodium phosphate dip (TSP), hot water dip (HWD) and their combination dip with/without brushing on broiler breast skin for bacterial reduction and structural changes. Eviscerated broiler carcasses were obtained from a local slaughter plant and immediately subjected to one of six treatments: 1) two tap water dips at 25 °C (TWD/TWD), 2) TWD/TWD with brushing (TWD/TWD/B), 3) TWD and TSP at 8%/25 °C (TWD/TSP), 4) TWD and HWD at 71 °C (TWD/HWD), 5) TSP and HWD (TSP/HWD), and 6) TSP/HWD with brushing (TSP/HWD/B). Each dip was conducted for 45 s with or without brushing at 5 s on/off during the second dip. Compared to the control (TWD/TWD), TSP/HWD significantly reduced mesophilic aerobic bacteria (MAB), Escherichia coli ( E. coli ), and total coliforms by 1.1, 0.9 and 1.0 log CFU/g, respectively, and Salmonella prevalence by 53.3% ( P  < 0.05), whereas TWD/TSP and TWD/HWD showed intermediate reductions ( P  < 0.05). Upon brushing, TSP/HWD/B reduced populations of MAB, E. coli, and total coliforms, and the prevalence of Salmonella more effectively than control of brushing (TWD/TWD/B) ( P  < 0.05). When two sampling methods were compared, the method of stomaching released fewer MAB and total coliforms (named loosely-associated cells) than the grinding of the stomached skin (named tightly-associated cells). Compared to controls (TWD/TWD and TWD/TWD/B), both TSP/HWD and TSP/HWD/B generally resulted in darker, less reddish, and more yellowish breast skin. Scanning electron microscope and histological images indicated that both TSP/HWD and TSP/HWD/B had deeper skin penetration than controls or TWD/HWD and TWD/TSP. Overall, TSP/HWD/B showed the most effectiveness in broiler carcass decontamination. Highlights: Physical and chemical interventions were evaluated for decontamination on broiler. Combined intervention resulted in better results than any single application. SEM and histological images supported the outcomes of better decontamination. However, the combination changed the broiler skin color negatively.